Farmers' perceptions and adaptation strategies to climate change in Punjab agriculture - KUMAR, SUNNY; SIDANA, BALJINDER KAUR (The Indian Journal of Agricultural Sciences, 2018)
Climate change is affecting the performance of agriculture. Farmers are the hardest hit as they have to continuously respond to climate variations. In order to know the farmers' perceptions about climate change and the adaptation strategies the present study collected the primary data from 200 farmers from different agro-climatic zones of Punjab. Multinomial logit model was used to identify the factors affecting the adaptation of climate resilient technologies. The findings revealed that most of the farmers (77%) perceived decrease in seasonal rainfall while 53% of them perceived decrease in rainfall in rabi season. Majority of the farmers (83.5% in kharif and 93% in rabi) perceived that temperature is higher than before. The adaptation choices mostly practiced by sample farmers were laser levelling of the field and improvement in irrigation structures, which was adopted by 30 and 27% of total adoption respectively. The regression model discerned determinants affecting adaptation choices were, viz. age, education, farm size, perception on temperature and extension lectures. Adaptation to climate change is constrained by several factors such as lack of knowledge about technology, lack of finance and credit availability and inadequate trainings and demonstrations about the climate resilient technologies.